Fingerprinting blank paper using commodity scanners - Clarkson, William; Weyrich, Tim; Finkelstein, Adam; Heninger, Nadia; Halderman, J. Alex; Felten, Edward W. (Proceedings - IEEE Symposium on Security and Privacy, 2009)
This paper presents a novel technique for authenticating physical documents based on random, naturally occurring imperfections in paper texture. We introduce a new method for measuring the three-dimensional surface of a page using only a commodity scanner and without modifying the document in any way. From this physical feature, we generate a concise fingerprint that uniquely identifies the document. Our technique is secure against counterfeiting and robust to harsh handling; it can be used even before any content is printed on a page. It has a wide range of applications, including detecting forged currency and tickets, authenticating passports, and halting counterfeit goods. Document identification could also be applied maliciously to de-anonymize printed surveys and to compromise the secrecy of paper ballots. © 2009 IEEE.
CRIS-Team Scopus Importer:2022-07-26